FORMATION OF INDIVIDUALLY-PERSONAL QUALITIES OF STUDENTS OF UNIVERSITIES OF THE MINISTRY OF EMERGENCY MEASURES OF RUSSIA ON THE BASIS OF PERSONALITY-ACTIVITY APPROACH - Alexey V. Ermilov (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Each special disciplines taught future specialists in the field of fire fighting equipment at the University of the EMERCOM has its essential features, the study of which is indispensable for the formation of the personality of cadets. Teaching them in the form of practical classes at the training and rescue centers, increasing the likelihood that more cadets acquire the knowledge, skills and individual personal qualities needed for their performance. To enhance the effectiveness of training cadets universities EMERCOM us an attempt was made to use student-activity approach when carrying out practical exercises with cadets of the fourth year of study at the training center in Ivanovo RUSSIAN fire and rescue Academy SFS MES of Russia. The article deals with the main aspects of personality-active learning, as well as its pedagogical principles in practical training of cadets. To review the effectiveness of this method of training has been conducted two experiments. At the end of the school year, we surveyed the cadets on two fronts. In one of the experiments we evaluated the development interest for trainees to study the practical component of special disciplines, in particular their desire to be on fire officials. In the second experiment, we examined how the representation of cadets on individually-personal qualities of the head of the fire. The study concluded that the application of the student-activity approach when carrying out practical exercises based on training and rescue centers not only stimulates intellectual activity and generates individual personal qualities, but also develops the motivation of cadets to the mastery of their chosen profession.